2020
DOI: 10.3390/ijms21217980
|View full text |Cite
|
Sign up to set email alerts
|

Virus–Host Protein–Protein Interactions between Human Papillomavirus 16 E6 A1 and D2/D3 Sub-Lineages: Variances and Similarities

Abstract: High-risk strains of human papillomavirus are causative agents for cervical and other mucosal cancers, with type 16 being the most frequent. Compared to the European Prototype (EP; A1), the Asian-American (AA; D2/D3) sub-lineage seems to have increased abilities to promote carcinogenesis. Here, we studied protein–protein interactions (PPIs) between host proteins and sub-lineages of the key transforming E6 protein. We transduced human keratinocyte with EP or AA E6 genes and co-immunoprecipitated E6 proteins alo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 123 publications
(188 reference statements)
0
7
0
Order By: Relevance
“…This could indicate that these candidates have limited binding affinity to the endogenous E6 protein. Based on our results with C26, such sdAbs likely bind the folded E6 protein but E6 is also known to interact with 50 or more host proteins (summarized in Dayer et al 2020 with references therein) using residues distributed throughout the protein. This means that any molecule targeting E6 must compete with host proteins.…”
Section: Discussionmentioning
confidence: 76%
“…This could indicate that these candidates have limited binding affinity to the endogenous E6 protein. Based on our results with C26, such sdAbs likely bind the folded E6 protein but E6 is also known to interact with 50 or more host proteins (summarized in Dayer et al 2020 with references therein) using residues distributed throughout the protein. This means that any molecule targeting E6 must compete with host proteins.…”
Section: Discussionmentioning
confidence: 76%
“…Furthermore, the Wnt/β-catenin pathway has been shown to increase the Warburg effect by suppressing mitochondrial respiration by reducing cytochrome oxidase transcription, an essential enzyme for OXPHOS [154]. On the other hand, AA sublineage variants increase mTOR activation, which, like the Wnt/β-catenin pathway, leads to energy metabolism activation through HIF-1α [13]. The E6 variant E-A126 with the R8Q mutation promotes the glycolytic pathway by activating the Wnt/β-catenin pathway.…”
Section: Activation Of Signaling Pathways That Regulate Glycolysismentioning
confidence: 99%
“…One of the ways that could also be participating in the positive regulation of glycolysis through the AA sublineage variant is by binding to the gamma-2 subunit of the protein kinase activated by 5'-AMP On the other hand, the Asian variant of E6, containing the amino acid change D25E in the E6 oncoprotein, negatively regulates the expression of the AIFM2 protein [16], known as apoptosis-inducing factor mitochondria associated 2, which contains a domain oxidoreductase NADH [166]. It has also been observed that the variant of the AA sublineage binds to cytochrome C [13] and could be interfering at levels such as the Asian variant D25E [13,16,167], which also increases the expression levels of ENO1 (Figure 4) [16]. The low levels of AIFM2 and cytochrome C, as well as the increase in the expression of ENO1 induced by the variant AA and As, may affect the reduction of oxidative phosphorylation, favoring the production of energy through aerobic glycolysis, one of the main characteristics of metabolic reprogramming in cancer.…”
Section: Regulation Of Metabolic Enzymesmentioning
confidence: 99%
See 2 more Smart Citations